Built for people! Corporate social responsibility of contractors: a special reference to the Malaysian construction industry - Sufian, Azlinor; Abdul Ghadas, Zuhairah Ariff (Sweet & Maxwell Asia, 2008)
In Malaysia, top of the chart on consumer complaints has long been hold by the ‘contractors’ particularly the house developers. Nearly every day, viewers of the Prime News are exposed to grievances of house buyers, be it late delivery or non delivery of vacant possession, safety of the building, defective building, incomplete/abandoned work, no certificate of fitness of occupation, misrepresentations and issues relating to environmental such as pollution and nuisance. Despite continuous complaints by house buyers, non-profit organizations (NGOs), consumer associations and environmentalists, housing projects particularly the residential home proceeded as usual (if not more) in the amidst of the unresolved issues.